THE DEVELOPMENT OF ACTIVITY PACKAGE USING FOLK LITERATURE BASED TO ENHANCE THAI TEACHING READING, WRITING AND ANALYTICAL THINKING SKILLS FOR PRIMARY LEVEL IN BANGKOK - Jaipukdee, Pratchaya (Academic Journal Phranakhon Rajabhat University, 2024)
The purposes of this research were to: 1) develop a folk literature-based activity package for Thai language instruction, and 2) assess the effectiveness of this activity package on Thai language teachers' teaching skills in reading, writing, and analytical thinking, as well as on learners' skills in these areas. The sample consisted of 12 teachers who teach basic Thai language at the primary education level in Bangkok, regardless of their affiliation, who were willing to receive supervision and follow-up, and 360 primary education students in Bangkok selected through simple random sampling. The research instruments included lesson plan evaluation forms, teaching skills evaluation forms, pretests, and posttests. The data were analyzed using mean and standard deviation. The research findings indicated that: 1) the developed activity package had an appropriateness value at the highest level and met the efficiency criteria of 80/80, 2) the assessment of the teachers' use of the activity package showed improvements in lesson plans, with pre-experiment scores (x̅ = 3.32, S.D. = 0.41) and post-experiment scores (x̅ = 4.33, S.D. = 0.44). Similarly, teaching skills improved from pre-experiment scores (x̅ = 3.26, S.D. = 0.42) to post-experiment scores (x̅ = 4.41, S.D. = 0.37). Lastly, the assessment of learners’ skills in reading, writing, and analytical thinking revealed that posttest scores were significantly higher than pretest scores, with a statistical significance level of p < .05.